Exploring Ethnography in The Muram Batu’s Anthology Hujan Kota Arang - Donny Adiatmana Ginting (Institut Agama Islam Negeri Palopo, 2023)
This research explores the ethnographical values in the Muram Batu’s book Hujan Kota Arang. The ethnographical values refer to the human culture, faith, belief, and language depicted in the literature, such as a short story. The author used universal categories of culture proposed by Clyde Kluckhohn consists of language, knowledge systems, social organizations, living and technological equipment systems, livelihood systems, religion, and the arts.This research is library research, and the research design is descriptive qualitative research. The author used content analysis and descriptive analysis to analyze the ethnographical elements in each short story. The result shows the ethnographical features depicted are language, social organization, religion and the arts. The language is revealed in the story of coffee shop, analieoita and dugan ragi manis. The social organization revealed in the the nemui nyimah and a story of the coffee shop. The religion is depicted in in the anaileoita and the death of sipatitik. The arts depicted in the dugan ragi manis.